High-intensity interval vs moderate-intensity continuous exercise in heated water-based on acute hemodynamic, vascular, and cardiac autonomic responses in older individuals with hypertension. (11th May 2021) - Roque Marcal, I; Amaral, VT; Fernandes, B; Abreu, RM; Guimaraes, GV; Ciolac, EG
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP #2017/25648-4 #2018/09695-5) and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES – Finance Code 001). OnBehalf: Exercise and Chronic Disease Research Laboratory (ECDR) Introduction: Post-exercise hypotension is an important tool in the treatment and control of hypertension. In recent years, high-intensity interval exercise (HIIE) has gained significant popularity in exercise-based prevention and rehabilitation of clinical populations. However, to date, it is not clarifying the acute responses of exercise performed in heated water-based in older individuals with hypertension. Purpose: To assess hemodynamic, vascular, and cardiac autonomic responses to heated water-based HIIE versus moderate-intensity continuous exercise (MICE) in older individuals with hypertension. Methods: Twenty older individuals (67 ± 7 y) under treatment for hypertension were randomly assigned to perform HIIE (25 min), MICE (30 min) and control (CON; 30 min) sessions in a heated swimming pool (30-32ºC). Blood pressure (BP), arterial stiffness, endothelial reactivity, and heart rate variability (HRV) were measured before (PRE), immediately after (POST), and after 45 min (REC). 24-h ambulatory BP monitoring and ambulatory HRV were also performed after each intervention. HRV were analyzed in ms² (ms²) or normalized units (nu) and then converted into natural logarithms (ln). Time domain markers as mean of intervals R-R (µi-RR), and frequency domain such as high frequency band (HF) and low frequency band (LF). Results: Systolic BP increased at POST (p < 0.05) in all interventions, with higher increases in CON (29 ± 3 mmHg) and MICE (19 ± 3 mmHg) than HIIE (9 ± 4 mmHg). Although systolic BP reduced at REC in all interventions, it returned to levels similar to PRE in HIIE, and continue at higher levels than PRE in MICE and CON. HIIE promoted a higher response on markers of parasympathetic modulation at REC compared to MICE (HFln, nu 0.14 ± 0.06, p = 0.02) and CON (µi-RR: 0.02 ± 0.01, p = 0.05). By contrast, during night-time, HIIE demonstrated a lower parasympathetic modulation than CON (HFln, nu: -0.06 ± 0.03, p = 0.05). In addition, CON showed a higher HRV during 24-h compared to HIIE and MICE. Conclusion: Despite differences between interventions in BP and cardiac autonomic responses, heated water-based HIIE or MICE were not effective to improve hemodynamic and vascular responses. These results may have important implications in the management of older individuals with hypertension in heated water-based.